1993
DOI: 10.1161/01.cir.87.6.1921
|View full text |Cite
|
Sign up to set email alerts
|

Increased left ventricular mass after thoracotomy and pericardiotomy. A role for relief of pericardial constraint?

Abstract: Background. Myocardial stretch and increased ventricular filling can lead to increased rates of myocardial protein synthesis. In animal studies, left ventricular mass increases after pericardiectomy,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

1994
1994
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 43 publications
(13 reference statements)
0
11
1
Order By: Relevance
“…To our knowledge, no studies have investigated the effect of thoracotomy in the mouse on hemodynamic function at two time points. An effect of relief of pericardial constraint after pericardectomy could play a role, as it has been described that LV dilation and hypertrophy occurs in humans after pericardectomy (22). However, in the present study, no LV remodeling was observed in the sham group at 8 wk and no significant differences were observed between sham and control animals at 8 wk.…”
Section: Discussioncontrasting
confidence: 67%
“…To our knowledge, no studies have investigated the effect of thoracotomy in the mouse on hemodynamic function at two time points. An effect of relief of pericardial constraint after pericardectomy could play a role, as it has been described that LV dilation and hypertrophy occurs in humans after pericardectomy (22). However, in the present study, no LV remodeling was observed in the sham group at 8 wk and no significant differences were observed between sham and control animals at 8 wk.…”
Section: Discussioncontrasting
confidence: 67%
“…In our study we have shown that there was significant decrease of scar tissue, a corresponding increase in viable tissue and an increase in regional contractile performance (as measured by both systolic wall thickening and tissue tagging), which together yielded a significant increase of global LVEF. The seemingly paradoxical simultaneous increase in EDV and LVEF, which is well described in other trials post-CABG 24, 25, 32 , is attributable to the interactions of an intact pericardium (or the lack thereof post-surgery) and the ventricular hemodynamics 33 without directly affecting the contractile performance 32, 34 .…”
Section: Discussionmentioning
confidence: 64%
“…17 Pericardial resection in animals and humans is associated with mild, balanced increases in LV dimension and mass. 17, 30 This modest increase in chamber size, if confirmed in chronic animal studies and in humans, would be expected to improve forward stroke volume and cardiac output, which limit exercise capacity in many patients with HFpEF. 6 …”
Section: Discussionmentioning
confidence: 95%